KANIBALISME PARTAI POLITIK ISLAM DI KOTA SURABAYA PADA PEMILU 2014 - Palestina, Firdaus Ayu (Jurnal Review Politik, 2015)
The focus of this paper is the phenomenon of the decline of votes at every election as well as the causes of cannibalism that occurred between Islamic parties in the 2014 elections. In this thesis uses qualitative research with descriptive research method. The results of this thesis study is known that the cause of the decline of Islamic party; Fusion and the history that accompanied political parties. Factors Islamic party of the less successful "galvanize" the militant cadres and their capability. Factors party candidates who left the party's vision and sacred mission to make it do a black campaign. Meanwhile, related to the causes of the phenomenon of cannibalism politics here the results obtained three factors, namely: common denominator mass base traditionalists who owned each Islamic party, the factor of voter behavior is dominated by rational voters, a factor difference programs in every region of the election, and the last factor was unclear who owned the principle of Islamic parties.